Cost‑effectiveness analysis of hexaminolevulinate (Hexvix®) guided cystoscopy in Non‑Muscle Invasive Bladder Cancer patients (NMIBC) in Italy - Bennison, Craig; Stephens, Stephanie; Conti, Giario Natale (Farmeconomia. Health Economics and Therapeutic Pathways, 2014)
OBJECTIVE: To estimate the incremental cost‑effectiveness of hexaminolevulinate (Hexvix®) + Blue Light (H+BL) cystoscopy (compared to white light cystoscopy only) when used at initial transurethral resection of the bladder tumour (TURBT) for patients diagnosed with non‑muscle invasive bladder cancer (NMIBC) in Italy. METHODS: A cost‑effectiveness model has been developed to estimate the incremental cost‑effectiveness of introducing H+BL at initial TURBT for patients diagnosed with NMIBC in Italy. The model consists of two parts: 1) a short term decision tree which estimates the outcome of the initial diagnostic procedure, and 2) a Markov cohort model which is used to estimate long term outcomes through extrapolation based on data and assumptions about patient management, the natural history of the disease and the empirical efficacy of H+BL in improving diagnosis detection and reducing recurrence. Cost‑effectiveness results are expressed as incremental costs per QALY gained. Univariate and probabilistic sensitivity analyses are conducted to test the robustness of the model to changes in inputs and assumptions. RESULTS: Base case results suggest that Hexvix® is a dominant strategy when used in the resection of NMIBC. Hexvix® is expected to be associated with 0.070 incremental QALYs, with cost savings of € 435 per patient. Sensitivity analyses suggest that the cost of Hexvix® and the relative risk of recurrence in intermediate and low risk groups are key drivers in the model. Probabilistic analyses indicate that Hexvix® is expected to be cost‑effective in >99% of iterations, assuming a willingness to pay threshold of € 25,000 per QALY. CONCLUSION: In conclusion, Hexvix® is expected to be a cost‑effective strategy when used in the resection of NMIBC in Italy.